HLY1104 Winter Cruise Zooplankton Abundance and Composition Data - Carin Ashjian; Robert G Campbell; Stephen Okkonen (Arctic Data Center, 2014)
Zooplankton abundance and composition data collected during the USCGC Healy cruise to the Chukchi, Beaufort, and Bering Seas in Nov. - Dec. 2011. This contains the mesozooplankton abundances from plankton tows using both paired Bongo nets and a Hydrobios Multinet conducted at stations in the Chukchi, Beaufort, and Bering Seas during November and December of 2011. The reader is referred to the event log for this cruise that is posted also at the data archive for additional information on the date, time, and location of each station/sample. There are six data files archived here, two excel files and four ascii files (.txt). The Excel files (HLY1104_Zooplankton_150um and HLY1104_Zooplankton_53um) contain abundances as #/m2 in the first sheet, as well as station information (date, time, location, net depth interval, sea floor depth), and definition of the abbreviations used for the species/taxa in the second sheet for samples collected using 150 µm and 53 µm mesh nets. The ascii files HLY1104_Zooplankton_150um.txt HLY1104_Zooplankton_53um.txt contain the abundances as #/m2 and station information. The text files HLY1104_Zooplankton_150um_Abbreviations.txt and HLY1104_Zooplankton_53um_Abbreviations.txt contain definition of the abbreviations used in the data file. See ZooplanktonMethods (.txt and .doc) for more details and methodology.